Long-term directional changes in urban bird communities of Mar del Plata City, Argentina - Leveau, Lucas M. (Frontiers in Ecology and Evolution, 2024)
Urban environments have been characterized by their temporal stability of resources, which could promote stability in bird composition. Several studies have found that bird communities in urban environments persist over the years, showing a similar species composition in the short term. However, studies analyzing continuous changes in urban communities over the long term are scarce. This study aimed to analyze the stability or directional changes (instability) in bird communities along an urban gradient. Bird counts were conducted in urban, suburban, and periurban areas over 8-10 years in 2002-2019. Changes in species composition were analyzed over periods ranging from one year to the next, to changes from one year to the seventeenth. Urban bird communities were more similar between years than suburban and periurban communities. Compositional changes were greater as time lags increased, indicating directional compositional shifts. The magnitude of these changes was similar across the urban gradient. The Chimango Caracara (Milvago chimango), the Picazuro Pigeon (Patagioenas picazuro), the Rufous Hornero (Furnarius rufus), and the Red-bellied Thrush (Turdus rufiventris) significantly increased their abundances during the period, while the House Sparrow (Passer domesticus) significantly decreased its abundance. Regional changes in species abundance, urban vegetation succession, and biotic interactions could explain the changes in bird communities.